Complex model of market price development and its simulation - Stádník, Bohumil; Miečinskienė, Algita (Journal of Business Economics and Management, 2015)
The purpose of this study is to suggest a complex model of market price development for liquid assets, which is able to simulate all of the main features particular to the real price development and has a realistic financial explanation. First, the paper defines assumptions for the model construction from empirically observed processes. Then, the model is implemented in the real simulation environment. Finally, the ability of the model is checked to simulate empirically observed features, e.g. leptokurtic characteristics or skewness of the price distribution. Also, this paper newly defines and implements the resonance effect. FFT analysis is used to support oscillation processes. Finally, selected markets are provided with parameter optimisation of the model based on empirical observations. It was found that the model built under the previously mentioned assumptions was able to explain empirically observed effects that reversely support the correctness of those assumptions. The practical value of the constructed model can be found in many areas, including risk management and asset valuation.